Manganese-Enhanced Magnetic Resonance Imaging: Overview and Central Nervous System Applications With a Focus on Neurodegeneration - Cloyd, Ryan A. (Front Aging Neurosci, 2018)
Manganese-enhanced magnetic resonance imaging (MEMRI) rose to prominence in the 1990s as a sensitive approach to high contrast imaging. Following the discovery of manganese conductance through calcium-permeable channels, MEMRI applications expanded to include functional imaging in the central nervous system (CNS) and other body systems. MEMRI has since been employed in the investigation of physiology in many animal models and in humans. Here, we review historical perspectives that follow the evolution of applied MRI research into MEMRI with particular focus on its potential toxicity. Furthermore, we discuss the more current in vivo investigative uses of MEMRI in CNS investigations and the brief but decorated clinical usage of chelated manganese compound mangafodipir in humans.